TINJAUAN PERLINDUNGAN HUKUM TERHADAP PENGGUNA PINJAMAN ONLINE ILEGAL - Alvina Septitania (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This journal reviews how changes in legal protection against users who are trapped in terms and regulations for illegal online loans generally harm their users. The research method used is juridical normative with analytical descriptive research specifications and with an invited-invited approach (sculpture approach). The application that connects the borrower and the party lending it, the credit and / or loan agreement that should be between these parties must refer to Article 1320 of the Civil Code, so that from the start of the submission process, agreeing between the borrower and the lender, and which disbursements are made online and supported only by lever incoming messages via cell phone without meeting and face to face. The risks that arise in illegal online loans are high interest rates, high fines, and leakage of personal data.